“IT’S A NATURAL PROCESS AND WE SHOULD ACCEPT IT AS OUR DESTINY”: INDONESIAN WOMEN PERCEPTION TO MENOPAUSE - Farida Kartini; Hikmah Hikmah (Belitung Nursing Journal, 2017)
Background: The changes in menstrual cycle are commonly followed by symptoms such as hot flushes, palpitations, sleep disorders, depression, irritability, headaches and low sexual drive in women. Women’s knowledge and perception to their menopause cyclic changes are important in their adaptation to menopause symptoms. Objective: This study aims to assess women’s perception toward menopause. Methods: This study employed a qualitative research design with phenomenology approach. Nine married women aged 45-55, residing in Ngestiharjo, Bantul district, Daerah Istimewa Yogyakarta, Indonesia participated in this research. Results: Respondents perceived menopause as a natural event for every woman above 45 years old and therefore it should be accepted as it is. Participants of the study defining menopause as a period when ovaries naturally end producing sexual hormone resulting with no menstrual periods for 12 consecutive months without other identified biological or physiological causes. The participants understand the basic knowledge of menopause and remarked their menopause period with muscular pain and irregular flows. In practice, as well as other menopausal women, respondents also experienced vaginal pains during coitus. Conclusion: Women of the study acknowledged that menopause as the end of their reproductive period. It is believed as a natural event and will be experienced by every woman. Nevertheless, women’s misconception and belief to menopause myths alarms the need for an adequate information related healthy menopause. Women preparedness is expected to reduce the symptoms and disorders following menopause.